Phase equilibria studies in the CaO–SiO2–Al2O3–MgO system with CaO/SiO2 ratio of 0.9. Issue 12 (28th August 2020) - Wang, Dongqing; Chen, Mao; Jiang, Yang; Wang, Shuai; Zhao, Zhixing; Evans, Tim; Zhao, Baojun
Abstract: Phase equilibria and liquidus temperatures in the CaO–SiO2 –Al2 O3 –MgO system at a CaO/SiO2 weight ratio of 0.9 in the liquid phase have been experimentally determined employing high‐temperature equilibration and quenching technique followed by electron probe X‐ray microanalysis. Isotherms at 1573, 1623, 1673, and 1773 K were determined and the primary phase fields of wollastonite, melilite, olivine, periclase, spinel, and corundum have been located. Compositions of the olivine and melilite solid solutions were analyzed and discussed. Comparisons between the newly constructed diagram, existing data, and FactSage predicted phase diagrams were performed and differences were discussed. The present study will be useful for guidance of industrial practices and further development of thermodynamic modeling.